Comparative organellar genomics of Arundina graminifolia: mitochondrial complexity and plastid conservation in Orchidaceae - Lin, Shengnan; Song, Chao; Wang, Jie; Kong, Jiali; Peng, Dan; Gao, Jie; Wu, Zhiqiang (Frontiers in Plant Science, 2026)
Orchidaceae is one of the largest and most diverse angiosperm families, exhibiting remarkable morphological and ecological diversity. Organellar genomes, including mitochondrial and plastid genomes, play essential roles in energy metabolism, photosynthesis, and adaptive evolution, yet their structural evolution in orchids remains unclear. In this study, the mitochondrial and plastid genomes of Arundina graminifolia were assembled and compared with 15 representative orchid species to investigate genome architecture, repeat content, gene composition, and evolutionary dynamics. The mitochondrial genome of A. graminifolia displayed a complex multi-circular structure with extensive rearrangements and abundant repeats, including simple sequence repeats and long repeats, contributing to genome expansion and structural complexity. In contrast, the plastid genome was highly conserved, exhibiting a typical quadripartite structure. Plastid-to-mitochondrion DNA transfers (MTPTs) varied among orchid species in both number and composition, mainly involving complete plastid genes associated with photosynthesis and translation. Analyses of selection pressure and nucleotide diversity revealed strong purifying selection and low sequence variability in mitochondrial genes, whereas plastid genes exhibited higher diversity and evolutionary rates. Phylogenetic analyses based on conserved single-copy genes from both organellar genomes yielded congruent topologies, with A. graminifolia clustering closely with Bletilla striata. Synteny analysis indicated low conservation of mitochondrial genome organization across lineages, particularly in mycoheterotrophic orchids, reflecting dynamic genome evolution. Gene loss and duplication further enhanced genome plasticity and potential functional redundancy. Overall, this study highlights contrasting evolutionary constraints and structural dynamics between mitochondrial and plastid genomes in orchids, providing valuable genomic resources for understanding organelle genome evolution and phylogenetic relationships in Orchidaceae.